Association between serum cotinine levels and urinary incontinence in adults in the United States: a population-based cross-sectional analysis - Chengdong Shi; Lei Yang; Guoqiang Zeng; Hongliang Cao; Fangqiu Yu; Shanyu Sha; Yuantao Wang (BMC, 2024)
Abstract Environmental tobacco smoke (ETS) exposure has been shown to be associated with a variety of diseases, but evidence regarding the association between it and urinary incontinence (UI) is limited. Cotinine, a metabolite of nicotine in the human body, can more accurately quantify the level of human exposure to tobacco smoke. The study utilized data from seven survey cycles (2007-March 2020 Pre-pandemic) of the National Health and Nutrition Examination Survey (NHANES) program. Weighted multivariable logistic regression analysis, subgroup analysis, interaction tests, smooth curve fitting, and threshold effect models were used to analyze the relationship between serum cotinine and UI. Additionally, a 1:1 nearest neighbor propensity score matching (PSM) method was employed to minimize the impact of confounding factors. Before and after PSM, serum cotinine levels were higher in individuals with UI than those without (P < 0.05). Both before and after PSM, UI was positively correlated with serum cotinine levels, with a significantly increased risk of urinary incontinence when serum cotinine levels were in the Q3 range (before PSM: OR = 1.89, 95% CI = 1.59-2.24; after PSM: OR = 1.60, 95% CI = 1.28-2.00). Smooth curve fitting before and after PSM showed an approximate J-shaped non-linear dose-response relationship between log-transformed serum cotinine levels and UI. This study indicates that among American adults, there is a positive relationship between serum cotinine levels and UI, which is also significant in self-reported non-smoking populations. Therefore, reducing exposure to environmental tobacco smoke (e.g., avoiding second-hand smoke) in work and daily life may help alleviate the occurrence of UI, and serum cotinine levels have the potential to be a tool for predicting the degree of risk of developing UI.